Thermoplastic polyurethane composite material fast neutron conversion screen and preparation method thereof
Preparing surface-modified phosphor distribution in thermoplastic polyurethane by in-situ polymerization, the problem that existing fast neutron conversion screens cannot take into account both high sensitivity and high resolution, and realize high resolution and high brightness fast neutron conversion screens, improving the imaging quality of fast neutron photography.
Patent Information
- Application Number
- CN202411845913.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing fast neutron conversion screens cannot take into account both high sensitivity and high resolution, resulting in poor quality of fast neutron photography.
The fast neutron conversion screen of thermoplastic polyurethane composite material containing phosphor was prepared by in-situ polymerization method, and the surface modification technology was used to improve the luminous and dispersive properties of the phosphor, and achieve uniform distribution of the phosphor.
A thermoplastic polyurethane fast neutron conversion screen with high resolution and high brightness was obtained, which solved the problem of poor imaging quality in the prior art and improved the imaging quality of fast neutron photography.
Smart Images

Figure CN119751805A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of nondestructive testing photography of neutron detectors, and in particular to a fast neutron conversion screen made of thermoplastic polyurethane composite material and a preparation method thereof. Background Art
[0002] The neutron radiography system consists of three main parts: neutron source, collimator, and image detector system (including neutron fluorescence conversion screen). The key component for detecting the spatial distribution of neutrons passing through the sample is the position-sensitive neutron detector, which is called the neutron-fluorescence conversion screen in neutron radiography technology. The neutron-fluorescence conversion screen is actually a plate-shaped functional composite material of a certain thickness. Its function is to convert the neutron rays passing through the sample to the neutrons in the conversion screen into protons of a large number of hydrogen atoms in the material and the neutrons to form recoil protons. The recoil protons make the fluorescent material emit light, thereby producing a detectable material image on the photosensitive film.
[0003] The fast neutron conversion screen is a key component of fast neutron photography, and its performance directly affects the final image quality. At present, in the field of fast neutron photography, the fast neutron conversion screens used mainly include mixed pressed screens composed of polyethylene, polypropylene, epoxy resin, etc. and fluorescent materials (mostly zinc sulfide (Ag) or Gd2S2O), containing aromatic Benzene ring There are organic scintillators with different structures, array shifted wave fiber type fast neutron-fluorescence conversion screens, etc. Among them, the scintillator screen and array shifted wave fiber screen have high detection efficiency (high brightness), but low resolution (above 2mm), while the mixed pressure screen has high resolution (below 0.5mm) and low detection efficiency (low brightness). The above three types of fast neutron conversion screens cannot provide satisfactory photographic effects. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a thermoplastic polyurethane composite material fast neutron conversion screen and a preparation method thereof. The present invention prepares a thermoplastic polyurethane fluorescent conversion screen containing fluorescent powder by an in-situ polymerization method. The surface of the fluorescent powder is modified by an appropriate method to achieve uniform distribution of the fluorescent powder. Thus, a high-resolution, high-brightness thermoplastic polyurethane fast neutron conversion screen is obtained. The high-brightness and high-resolution thermoplastic polyurethane fast neutron conversion screen of the present invention is characterized in that the preparation of the fluorescent conversion screen includes a process of preparing a transparent polyurethane prepolymer by diisocyanate and oligomeric diols (polyether diols or polyester diols), an in-situ chain extension reaction process of the transparent polyurethane prepolymer and zinc sulfide fluorescent powder, and a thermoplastic fluorescent polyurethane composite material hot pressing molding process.
[0005] The present invention provides a method for preparing a transparent polyurethane prepolymer, characterized in that it comprises the following steps:
[0006] Step 1: Raw material pretreatment
[0007] Weigh a certain amount of polyether diol or polyester diol into a 250 ml three-necked flask, and use a water ring vacuum pump to evacuate and remove water at 110° C. for 1-2 hours; weigh a certain amount of silver-doped zinc sulfide phosphor ZnS:Ag, and use hydrogen peroxide or ammonia solution to modify the surface of the zinc sulfide phosphor to improve the luminescence performance of the zinc sulfide phosphor and its bonding and dispersion performance with polyurethane, and then place it in a vacuum oven at 80-100° C. for drying for 1-2 hours;
[0008] Step 2: Preparation of transparent polyurethane prepolymer
[0009] A certain amount of oligomeric diol is taken and put into a reactor equipped with a reflux condenser and a stirrer, diisocyanate is added according to a molar ratio of diisocyanate to oligomeric diol of 2.1-3.1:1.0, and a small amount of catalyst is added, stirred at room temperature (25-40°C) for 1 hour, slowly heated to 60-80°C and stirred for reaction for 2-5 hours, and nitrogen protection is used during the reaction process. After the reaction is completed, a bifunctional transparent polyurethane prepolymer is obtained.
[0010] Further, the diisocyanate includes toluene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), hydrogenated diphenylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), hexamethylene diisocyanate trimer (PHDI), lysine diisocyanate (LDI) or a combination thereof.
[0011] Furthermore, the oligomeric diols include polyester diols prepared by esterification reaction of ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, phthalic acid, adipic acid, halogenated phthalic acid, polyethylene glycol, polypropylene glycol, polytetrahydrofuran diol or phthalic anhydride or a combination thereof.
[0012] Furthermore, the silver-doped zinc sulfide phosphor ZnS:Ag includes silver-doped ZnS:Ag / Mn, ZnS:Ag / Cu, ZnS:Ag / Si or a combination thereof.
[0013] The present invention provides a transparent polyurethane prepolymer, which is characterized in that it is prepared by adopting the above-mentioned preparation method of the transparent polyurethane prepolymer.
[0014] The present invention provides a method for preparing a thermoplastic polyurethane composite material fast neutron conversion screen using the above-mentioned transparent polyurethane prepolymer, characterized in that it comprises the following steps:
[0015] Step 1: Preparation of pre-dispersed system of transparent polyurethane prepolymer and phosphor
[0016] A certain amount of zinc sulfide phosphor ZnS:Ag, transparent polyurethane prepolymer, dispersant, antioxidant, and solvent are fully dispersed in a high-speed disperser for 30-60 minutes to obtain a pre-dispersed system of transparent polyurethane prepolymer and phosphor, wherein the zinc sulfide phosphor ZnS:Ag, transparent polyurethane prepolymer, dispersant, antioxidant, and solvent are composed of the following weight percentages:
[0017]
[0018] Step 2: Chain extension of fluorescent polyurethane prepolymer
[0019] According to the formula of the fluorescent polyurethane prepolymer predispersion, the molar content of diisocyanate groups is calculated, and the corresponding low molecular weight chain extender is added to the predispersion system of the transparent polyurethane prepolymer and the fluorescent powder prepared in step 1 at room temperature;
[0020] The transparent polyurethane prepolymer and the pre-dispersed system of the fluorescent powder after quantitative reaction are weighed and the solvent in the reaction mixture is removed by vacuum distillation with a vacuum pump, followed by stirring at room temperature for 30 minutes, and then slowly heating to 70-90° C. and stirring for reaction for 2-5 hours, and then discharging the material and pelletizing to obtain in-situ polymerized thermoplastic polyurethane fluorescent composite material particles.
[0021] Step 3: Hot-pressing thermoplastic polyurethane fast neutron fluorescence conversion screen
[0022] The thermoplastic polyurethane fluorescent composite material particles obtained in step 2 are dried, preheated, placed in a certain plate mold on a flat vulcanizer for hot pressing, and then cold pressed, cooled and demolded, burrs repaired, and defects cleaned to obtain a thermoplastic polyurethane composite material fast neutron conversion screen of desired thickness.
[0023] Furthermore, the hot pressing process is first plasticizing at 160°C for 20 minutes, then hot pressing at 160°C for 5 minutes with a pressure of 10.0 MPa, and finally cold pressing at room temperature for 20 minutes.
[0024] The invention provides a thermoplastic polyurethane composite material fast neutron conversion screen, which is characterized in that it is obtained according to a method for preparing a thermoplastic polyurethane composite material fast neutron conversion screen.
[0025] Furthermore, the thickness of the thermosetting polyurethane neutron conversion screen is 0.1-8.00 mm. The greater the thickness, the higher the brightness, but the resolution decreases. Vice versa. Under the condition that the composition of the fluorescent polyurethane functional material is certain, the optimal balance between resolution and sensitivity can be adjusted by adjusting the thickness of the conversion screen.
[0026] In the reaction mixture composed of the above-mentioned multiple materials, diisocyanate and oligomeric diol are raw monomers for synthesizing polyurethane. The synthesized polyurethane is the base material of the conversion screen, and also plays the role of an adhesive, and is also a material for fast neutrons to produce recoil protons by nuclear reaction; the role of zinc sulfide phosphor is to convert the energy deposited by fast neutrons into visible light for easy development and photography; the purpose of surface modification of zinc sulfide phosphor is to improve the luminescent properties of phosphor and the bonding and dispersion properties with polyurethane prepolymer; the main role of the added solvent is to reduce the viscosity of the mixture with high powder content, and the role of the antioxidant is to prevent the oxidation and discoloration of the organic polymer; the role of the catalyst is to promote the condensation reaction between diisocyanate and diol; the chain extension process of polyurethane prepolymer adopts an in-situ chain extension process after mixing with zinc sulfide phosphor, so that the zinc sulfide phosphor can be evenly dispersed at a lower viscosity before forming a thermoplastic polyurethane polymer. The above-mentioned percentage range of the combination of these components, as well as the process conditions for the preparation of the thermoplastic polyurethane prepolymer and the in-situ chain extension process after mixing with the zinc sulfide phosphor are determined through a large number of experiments. The above-mentioned combination percentage and the thickness range of the conversion screen enable the fast neutron conversion screen of the present invention to have an excellent balance of high brightness, high resolution and formability.
[0027] Beneficial effects of the present invention:
[0028] The present invention provides a fast neutron fluorescence conversion screen and a preparation method thereof with the advantages of low cost, high brightness, high resolution, etc. At the same time, the screen is easy to shape and can be repeatedly processed and used. The screen can overcome the disadvantage of poor imaging quality of the existing fast neutron conversion screen under the conditions of low collimation ratio and high gamma background, and solve the problem that the existing fast neutron photographic conversion screen cannot take into account both high sensitivity and high resolution at the same time. The fast neutron conversion screen of the present invention is of great significance for improving the quality of fast neutron imaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A histogram of the fluorescence intensity of the composite film containing zinc sulfide phosphor before and after H2O2 treatment in Example 1 of the present invention;
[0030] Figure 2 Fluorescence spectrum detection diagram of thermoplastic polyurethane composite films with different contents of zinc sulfide phosphor in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The present invention provides a method for preparing a transparent polyurethane prepolymer, characterized in that it comprises the following steps:
[0032] Step 1: Raw material pretreatment
[0033] Weigh a certain amount of polyether diol or polyester diol into a 250 ml three-necked flask, and use a water ring vacuum pump to evacuate and remove water at 110° C. for 1-2 hours; weigh a certain amount of silver-doped zinc sulfide phosphor ZnS:Ag, and use hydrogen peroxide or ammonia solution to modify the surface of the zinc sulfide phosphor to improve the luminescence performance of the zinc sulfide phosphor and its bonding and dispersion performance with polyurethane, and then place it in a vacuum oven at 80-100° C. for drying for 1-2 hours;
[0034] Step 2: Preparation of transparent polyurethane prepolymer
[0035] A certain amount of oligomeric diol is taken and put into a reactor equipped with a reflux condenser and a stirrer, diisocyanate is added according to a molar ratio of diisocyanate to oligomeric diol of 2.1-3.1:1.0, and a small amount of catalyst is added, stirred at room temperature (25-40°C) for 1 hour, slowly heated to 60-80°C and stirred for reaction for 2-5 hours, and nitrogen protection is used during the reaction process. After the reaction is completed, a bifunctional transparent polyurethane prepolymer is obtained.
[0036] Further, the diisocyanate includes toluene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), hydrogenated diphenylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), hexamethylene diisocyanate trimer (PHDI), lysine diisocyanate (LDI) or a combination thereof.
[0037] Furthermore, the oligomeric diols include polyester diols prepared by esterification reaction of ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, phthalic acid, adipic acid, halogenated phthalic acid, polyethylene glycol, polypropylene glycol, polytetrahydrofuran diol or phthalic anhydride or a combination thereof.
[0038] Furthermore, the silver-doped zinc sulfide phosphor ZnS:Ag includes silver-doped ZnS:Ag / Mn, ZnS:Ag / Cu, ZnS:Ag / Si or a combination thereof.
[0039] The present invention provides a transparent polyurethane prepolymer, which is characterized in that it is prepared by adopting the above-mentioned preparation method of the transparent polyurethane prepolymer.
[0040] The present invention provides a method for preparing a thermoplastic polyurethane composite material fast neutron conversion screen using the above-mentioned transparent polyurethane prepolymer, characterized in that it comprises the following steps:
[0041] Step 1: Preparation of pre-dispersed system of transparent polyurethane prepolymer and phosphor
[0042] A certain amount of zinc sulfide phosphor ZnS:Ag, transparent polyurethane prepolymer, dispersant, antioxidant, and solvent are fully dispersed in a high-speed disperser for 30-60 minutes to obtain a pre-dispersed system of transparent polyurethane prepolymer and phosphor, wherein the zinc sulfide phosphor ZnS:Ag, transparent polyurethane prepolymer, dispersant, antioxidant, and solvent are composed of the following weight percentages:
[0043]
[0044] Step 2: Chain extension of fluorescent polyurethane prepolymer
[0045] According to the formula of the fluorescent polyurethane prepolymer predispersion, the molar content of diisocyanate groups is calculated, and the corresponding low molecular weight chain extender is added to the predispersion system of the transparent polyurethane prepolymer and the fluorescent powder prepared in step 1 at room temperature;
[0046] The transparent polyurethane prepolymer and the pre-dispersed system of the fluorescent powder after quantitative reaction are weighed and the solvent in the reaction mixture is removed by vacuum distillation with a vacuum pump, followed by stirring at room temperature for 30 minutes, and then slowly heating to 70-90° C. and stirring for reaction for 2-5 hours, and then discharging the material and pelletizing to obtain in-situ polymerized thermoplastic polyurethane fluorescent composite material particles.
[0047] Step 3: Hot-pressing thermoplastic polyurethane fast neutron fluorescence conversion screen
[0048] The thermoplastic polyurethane fluorescent composite material particles obtained in step 2 are dried, preheated, placed in a certain plate mold on a flat vulcanizer for hot pressing, and then cold pressed, cooled and demolded, burrs repaired, and defects cleaned to obtain a thermoplastic polyurethane composite material fast neutron conversion screen of desired thickness.
[0049] Furthermore, the hot pressing process is first plasticizing at 160°C for 20 minutes, then hot pressing at 160°C for 5 minutes with a pressure of 10.0 MPa, and finally cold pressing at room temperature for 20 minutes.
[0050] The invention provides a thermoplastic polyurethane composite material fast neutron conversion screen, which is characterized in that it is obtained according to a method for preparing a thermoplastic polyurethane composite material fast neutron conversion screen.
[0051] Furthermore, the thickness of the thermosetting polyurethane neutron conversion screen is 0.1-8.00 mm. The greater the thickness, the higher the brightness, but the resolution decreases. Vice versa. Under the condition that the composition of the fluorescent polyurethane functional material is certain, the optimal balance between resolution and sensitivity can be adjusted by adjusting the thickness of the conversion screen.
[0052] The thickness of the fast neutron conversion screen of the present invention is 0.1-8.0 mm, and the most preferred thickness is 1.0-3.0 mm. The main function of the fast neutron conversion screen is to convert the spatial distribution of fast neutrons that cannot be directly detected into the spatial distribution of visible light that can be detected. The fluorescence generated by the luminescent material zinc sulfide in the conversion screen is weakened according to the law of inversely proportional to the square of the distance on the one hand, and is also attenuated by the absorption of the screen material itself on the other hand. Therefore, the thickness of the fast neutron conversion screen should be selected to achieve a balance between sensitivity (detection efficiency) and resolution. After a large number of theoretical calculations and experiments, it is determined that the thickness of the fast neutron conversion screen is 1.0-3.5 mm.
[0053] Example 1
[0054] Firstly, a surface-modified zinc sulfide phosphor was prepared. 20 g of ZnS:Ag phosphor was weighed and mixed with 100 ml of hydrogen peroxide in a conical flask. The mixture was placed on a magnetic stirrer at 50°C for 4 hours and filtered. The filter residue was dried in a vacuum oven at 60°C for 4 hours to obtain a surface-modified phosphor. 12 g (0.006 mol) of polypropylene glycol PPG2000, which had been dehydrated in a vacuum oven at 110°C for 1 hour, 0.015 g of antioxidant 1010, catalyst dibutyltin dilaurate (DBTDL), and 2.83 g (0.01275 mol) of isophorone diisocyanate (IPDI) were quantitatively weighed and added into a three-necked flask. The mixture was stirred at room temperature for half an hour and then reacted at 60°C for 2 hours to obtain a transparent polyurethane prepolymer. The temperature was lowered to below 40°C, 1.5ml tetrahydrofuran was added, and the mixture was transferred to a dispersion cup. 15g of surface-modified phosphor and 0.1g of Span-80 were added, and the mixture was fully dispersed for 1h by a high-speed disperser, and then transferred to a 100ml three-necked flask. Then 0.805g of dipropylene glycol was added, and the mixture was stirred and reacted at 40°C for 30min, and then the mixture was heated to 60°C for 3 hours, and then stirred and reacted at 80°C for 1 hour to end the reaction. After completion, the product was poured into a polytetrafluoroethylene square plate, placed in a fume hood at room temperature to allow the solvent to evaporate for 24 hours, and then placed in a vacuum oven at 60°C for vacuum drying for 6h. The dried film was taken out and cut into particles with scissors to obtain thermoplastic polyurethane fluorescent composite material particles. Finally, the particles were placed in a plate mold frame with a cavity thickness of 2mm and placed on a flat vulcanizer for hot pressing. The hot pressing process was preheating at 160°C for 20min, hot pressing at 160°C for 8min, and a pressure of 10.0MPa; then cold pressing at room temperature for 20min. The thermoplastic polyurethane conversion screen with a zinc sulfide content of 50% and a thickness of 2 mm was obtained after cooling and demoulding. Figure 1 The fluorescence intensity bar graph of the composite film of zinc sulfide phosphor with a content of (16.6%) before and after H2O2 treatment of the present invention is shown. The thermoplastic polyurethane composite adopts in-situ chain extension polymerization method, and the zinc sulfide phosphor is treated with 7.5% hydrogen peroxide at 50°C for 4 hours. Figure 2Schematic diagram of fluorescence spectra of thermoplastic polyurethane composite films with different contents of zinc sulfide phosphor in Example 1 of the present invention, wherein the content of zinc sulfide phosphor is the weight percentage of the composite.
[0055] Example 2
[0056] First, a surface-modified zinc sulfide phosphor is prepared. 20 g of ZnS:Ag phosphor is weighed and mixed with 100 ml of 5% potassium permanganate aqueous solution in a conical flask, and then the mixture is placed on a magnetic stirrer at 50° C. for 4 hours, filtered, washed with water 4-5 times, and the filter residue is dried in a vacuum oven at 60° C. for 4 hours to obtain a surface-modified phosphor. 12 g (0.006 mol) of polypropylene glycol PPG2000, 0.015 g of antioxidant 1010, catalyst dibutyltin dilaurate (DBTDL), and 3.34 g (0.01275 mol) of 4,4-dicyclohexylmethane diisocyanate (HMDI) are quantitatively weighed and added into a three-necked flask, stirred at room temperature for half an hour, and then reacted at 60° C. for 2 hours to obtain a transparent polyurethane prepolymer. The temperature was lowered to below 40°C, 1.5ml tetrahydrofuran was added, and the mixture was transferred to a dispersion cup. 15.6g of surface-modified phosphor and 0.1g of Span-80 were added, and the mixture was fully dispersed for 1h by a high-speed disperser, and then transferred to a 100ml three-necked flask. Then 0.805g of dipropylene glycol was added, and the mixture was stirred and reacted at 40°C for 30min, and then the mixture was heated to 60°C for 3 hours, and then stirred and reacted at 80°C for 1 hour to end the reaction. After completion, the product was poured into a polytetrafluoroethylene square plate, placed in a fume hood at room temperature to allow the solvent to evaporate for 24 hours, and then placed in a vacuum oven at 60°C for vacuum drying for 6h. The dried film was taken out and cut into particles with scissors to obtain thermoplastic polyurethane fluorescent composite material particles. Finally, the particles were placed in a plate mold frame with a cavity thickness of 2mm and placed on a flat vulcanizer for hot pressing. The hot pressing process was preheating at 160°C for 20min, hot pressing at 160°C for 8min, and a pressure of 10.0MPa; then cold pressing at room temperature for 20min. The thermoplastic polyurethane conversion screen with a zinc sulfide content of 50% and a thickness of 2 mm was obtained after cooling and demoulding.
[0057] Example 3
[0058] Firstly, a surface-modified zinc sulfide phosphor was prepared. 20 g of ZnS:Ag phosphor was weighed and mixed with 100 ml of hydrogen peroxide in a conical flask. The mixture was placed on a magnetic stirrer at 50°C for 4 hours and filtered. The filter residue was dried in a vacuum oven at 60°C for 4 hours to obtain a surface-modified phosphor. 12 g (0.006 mol) of polytetrahydrofuran PTMG2000, which had been dehydrated in a vacuum oven at 110°C for 1 hour, 0.015 g of antioxidant 1010, catalyst dibutyltin dilaurate (DBTDL), and 3.34 g (0.01275 mol) of 4,4-dicyclohexylmethane diisocyanate (HMDI) were quantitatively weighed and added into a three-necked flask. The mixture was stirred at room temperature for half an hour and then reacted at 60°C for 2 hours to obtain a transparent polyurethane prepolymer. The temperature was lowered to below 40°C, 1.5ml of tetrahydrofuran was added and stirred, then poured out and transferred to a dispersion cup, 10.6g of surface-modified phosphor and 0.1g of Span-40 were added, and the mixture was fully dispersed for 1h by a high-speed disperser, and then transferred to a 100ml three-necked flask. Then 0.805g of dipropylene glycol was added, and the mixture was stirred and reacted at 40°C for 30min, then heated to 60°C for 3 hours, and stirred and reacted at 80°C for 1 hour to end the reaction. After completion, the product was poured into a polytetrafluoroethylene square plate, placed in a fume hood at room temperature to allow the solvent to evaporate for 24 hours, and then placed in a vacuum oven at 60°C for vacuum drying for 6h, the dried film was taken out, and cut into particles with scissors to obtain thermoplastic polyurethane fluorescent composite material particles. Finally, the particles were placed in a plate mold frame with a cavity thickness of 2mm and placed on a flat vulcanizer for hot pressing. The hot pressing process is preheating at 160°C for 20 minutes, hot pressing at 160°C for 8 minutes, and a pressure of 10.0 MPa, and then cold pressing at room temperature for 20 minutes. After cooling and demoulding, a thermoplastic polyurethane conversion screen with a zinc sulfide content of 40% and a thickness of 2 mm is obtained.
[0059] Example 4
[0060] First, a surface-modified zinc sulfide phosphor was prepared. 20 g of ZnS:Ag phosphor was weighed and mixed with 100 ml of hydrogen peroxide in a conical flask. The mixture was placed on a magnetic stirrer at 50° C. for 4 hours, filtered, washed with water 4-5 times, and the filter residue was dried in a vacuum oven at 60° C. for 4 hours to obtain a surface-modified phosphor. 12 g (0.006 mol) of polypropylene glycol PPG2000, which had been dehydrated in a vacuum oven at 110° C. for 1 hour, 0.015 g of antioxidant 1010, catalyst dibutyltin dilaurate (DBTDL), and 3.34 g (0.01275 mol) of 4,4-dicyclohexylmethane diisocyanate (HMDI) were quantitatively weighed and added into a three-necked flask. The mixture was stirred at room temperature for half an hour, and then reacted at 60° C. for 2 hours to obtain a transparent polyurethane prepolymer. The temperature was lowered to below 40°C, 1.5ml tetrahydrofuran was added, and the mixture was transferred to a dispersion cup. 10.6g of surface-modified phosphor and 0.1g of Span-80 were added, and the mixture was fully dispersed for 1h by a high-speed disperser, and then transferred to a 100ml three-necked flask. Then 0.805g of dipropylene glycol was added, and the mixture was stirred at 40°C for 30min, and then the mixture was heated to 60°C for 3 hours, and then stirred at 80°C for 1 hour to terminate the reaction. After completion, the product was poured into a polytetrafluoroethylene square plate, placed in a fume hood at room temperature to allow the solvent to evaporate for 24 hours, and then placed in a vacuum oven at 60°C for 6h. The dried film was taken out and cut into particles with scissors to obtain thermoplastic polyurethane fluorescent composite material particles. Finally, the particles were placed in a plate mold frame with a cavity thickness of 2mm and placed on a flat vulcanizer for hot pressing. The hot pressing process was preheating at 160°C for 20min, hot pressing at 160°C for 8min, and a pressure of 10.0MPa; then cold pressing at room temperature for 20min. The thermoplastic polyurethane conversion screen with a zinc sulfide content of 40% and a thickness of 2 mm was obtained after cooling and demoulding.
[0061] In Examples 5-8, the operation method is the same as in Example 2, but the thickness is changed to 0.5 mm, 1.0 mm, 1.5 mm, and 3 mm.
[0062] In Examples 9-12, the operation method is the same as in Example 4, but the thickness is changed to 0.5 mm, 1.0 mm, 1.5 mm, and 3 mm.
[0063] From the brightness of the phosphor screen tested by fast neutron photography, the factors affecting the brightness of the above 12 examples are mainly the content of zinc sulfide phosphor and the thickness of the screen. Therefore, in terms of brightness, Example 1 is equivalent to Example 2, and Example 3 is equivalent to Example 4. The thermoplastic polyurethane composite materials prepared by the methods of Example 2 and Example 4 are named ZSTPU-50% and ZSTPU-40% respectively. The relative brightness of the fast neutron conversion screen prepared by the methods of Examples 2, 4, 5-12 is shown in Table 1. The brightness of the commercially available polypropylene mixed pressure type phosphor screen is taken as 1 as a reference value.
[0064] Table 1 Relative brightness analysis results of ZSPU with different contents and thicknesses
[0065]
[0066] At the same time, the resolution of the thermoplastic polyurethane conversion screen is comparable to that of the existing commercially available polypropylene mixed pressure fast neutron conversion screen of the same thickness. It can be seen that the thermoplastic polyurethane conversion screen made by the in-situ polymerization method can maintain a relatively high resolution while greatly increasing the brightness and detection sensitivity. This is of great significance to improving the imaging quality in the field of fast neutron photography.
[0067] The present invention is described in detail above in combination with specific implementation methods and exemplary embodiments. The above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments; the above description cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, the technical solution of the present invention and its implementation methods may be subjected to a variety of equivalent substitutions, modifications or improvements, all of which fall within the scope of the present invention; the protection scope of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a transparent polyurethane prepolymer, characterized in that: The following steps are involved: Step 1: Raw material pretreatment Weigh a certain amount of polyether diol or polyester diol into a 250 ml three-necked flask, and use a water ring vacuum pump to evacuate and remove water at 110° C. for 1-2 hours; weigh a certain amount of silver-doped zinc sulfide phosphor ZnS:Ag, use hydrogen peroxide or ammonia solution to modify the surface, and then place it in a vacuum oven at 80-100° C. to dry for 1-2 hours; Step 2: Preparation of transparent polyurethane prepolymer A certain amount of oligomeric diol is taken and put into a reactor equipped with a reflux condenser and a stirrer, diisocyanate is added according to a molar ratio of diisocyanate to oligomeric diol of 2.1-3.1:1.0, and a small amount of catalyst is added, stirred at room temperature for 1 hour, slowly heated to 60-80°C and stirred for reaction for 2-5 hours, and nitrogen protection is used during the reaction process. After the reaction is completed, a bifunctional transparent polyurethane prepolymer is obtained.
2. The method for preparing a transparent polyurethane prepolymer according to claim 1, characterized in that: The diisocyanate includes toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, lysine diisocyanate or a combination thereof.
3. The method for preparing a transparent polyurethane prepolymer according to claim 1, characterized in that: The oligomeric diols include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, phthalic acid, adipic acid, halogenated phthalic acid, polyethylene glycol, polypropylene glycol, polytetrahydrofuran diol or polyester diols prepared by esterification of phthalic anhydride or a combination thereof.
4. The method for preparing a transparent polyurethane prepolymer according to claim 1, characterized in that: The silver-doped zinc sulfide phosphor ZnS:Ag includes silver-doped ZnS:Ag / Mn, ZnS:Ag / Cu, ZnS:Ag / Si or a combination thereof.
5. A transparent polyurethane prepolymer, characterized in that: The transparent polyurethane prepolymer is obtained by the preparation method of any one of claims 1 to 4.
6. A method for preparing a thermoplastic polyurethane composite material fast neutron conversion screen using the transparent polyurethane prepolymer according to claim 5, characterized in that: The following steps are involved: Step 1: Preparation of pre-dispersed system of transparent polyurethane prepolymer and phosphor A certain amount of zinc sulfide phosphor ZnS:Ag, transparent polyurethane prepolymer, dispersant, antioxidant, and solvent are fully dispersed in a high-speed disperser for 30-60 minutes to obtain a pre-dispersed system of transparent polyurethane prepolymer and phosphor, wherein the zinc sulfide phosphor ZnS:Ag, transparent polyurethane prepolymer, dispersant, antioxidant, and solvent are composed of the following weight percentages: Transparent polyurethane prepolymer 25-50% Zinc sulfide phosphor ZnS:Ag 40-70% Dispersant 0.05-1.5% Antioxidant 0.1-0.2% Solvent 5-15% Step 2: Chain extension of fluorescent polyurethane prepolymer According to the formula of the fluorescent polyurethane prepolymer predispersion, the molar content of diisocyanate groups is calculated, and the corresponding low molecular weight chain extender is added to the predispersion system of the transparent polyurethane prepolymer and the fluorescent powder prepared in step 1 at room temperature; The transparent polyurethane prepolymer and the pre-dispersed system of the fluorescent powder after quantitative reaction are weighed and the solvent in the reaction mixture is removed by vacuum distillation with a vacuum pump, followed by stirring at room temperature for 30 minutes, and then slowly heating to 70-90° C. and stirring for reaction for 2-5 hours, and then discharging the material and pelletizing to obtain in-situ polymerized thermoplastic polyurethane fluorescent composite material particles. Step 3: Hot-pressing thermoplastic polyurethane fast neutron fluorescence conversion screen The thermoplastic polyurethane fluorescent composite material particles obtained in step 2 are dried, preheated, placed in a certain plate mold on a flat vulcanizer for hot pressing, and then cold pressed, cooled and demolded, burrs repaired, and defects cleaned to obtain a thermoplastic polyurethane composite material fast neutron conversion screen of desired thickness.
7. The method for preparing a thermoplastic polyurethane composite material fast neutron conversion screen according to claim 6, characterized in that: The hot pressing process is to first plasticize at 160°C for 20 minutes, then hot press at 160°C for 5 minutes with a pressure of 10.0 MPa, and finally cold press at room temperature for 20 minutes.
8. A thermoplastic polyurethane composite material fast neutron conversion screen, characterized in that: The fast neutron conversion screen made of thermoplastic polyurethane composite material is obtained by the preparation method of claim 7.
9. The thermoplastic polyurethane composite fast neutron conversion shield according to claim 8, characterized in that: The thickness of the thermosetting polyurethane neutron conversion screen is 0.1-8.00mm.
Citation Information
Patent Citations
Cubic crystal zinc sulfide nano-particles and nanocomposite optical thin film prepared thereby
CN101817549A
Method for preparing quantum dot / polyurethane nano crystal composite
CN101906249A
Fast neutrons fluorescent screen and preparation method thereof
CN103113670A
Production method of solidifiable transparent anti-yellowing polyurethane prepolymer
CN103396526A
In-situ preparation of TPU light conversion luminous film
CN104109225A